Analisis Yuridis Penghapusan Rintisan Sekolah Bertaraf Internasional (RSBI) Di Kota Batam - Rina Shahriyani Shahrullah; Wagiman Wagiman; Adi Kusuma (Journal of Judicial Review, 2014)
This study discussed about the effectivity of The Constitutional Court Verdict Number 5 Year 2012 about International Schools Pioneer (RSBI) Elimination at Batam City implementation. This research was formulated by a few problems because of the implementation of The Constitutional Court Verdict Number 5 Year 2012 about International Schools Pioneer (RSBI) Elimination especially at Batam City and the solutions to education performance pasca the verdict. The result showed that there were effects after The Constitutional Court Verdict Number 5 Year 2012 about International Schools Pioneer (RSBI) Elimination at Batam City.This study also analysed the solution to do the education activities at Batam City pasca The Constitutional Court Verdict Number 5 Year 2012 about International Schools Pioneer (RSBI) Elimination. The analysis showed that it was needed to prioritize the education quality increasement effort for the students through Superior School Programs and increase the roles of the stakeholders in helping the mandated Education National Standard fulfillment effort.